Post‐thrombolytic blood pressure and symptomatic intracerebral hemorrhage. (16th August 2016) - Waltimo, T.; Haapaniemi, E.; Surakka, I. L.; Melkas, S.; Sairanen, T.; Sibolt, G.; Tatlisumak, T.; Strbian, D.
Abstract : Background and purpose: Most guidelines for intravenous thrombolysis (IVT) in acute ischaemic stroke patients advise keeping systolic blood pressure (BP) below 180/105 mmHg prior to the bolus injection. Less is known about optimal management of BP thereafter. We assessed temporal changes in post‐thrombolytic systolic BP values and their impact on development of symptomatic intracerebral hemorrhage (sICH). Methods: The study cohort included 1868 consecutive acute ischaemic stroke patients treated with IVT at the Helsinki University Central Hospital. sICH was defined according to the European Cooperative Acute Stroke Study II (ECASS‐II) (primary outcome), National Institute of Neurological Disorders and Stroke, and Safe Implementation of Thrombolysis in Stroke criteria. We evaluated BP at admission, prior to IVT and at 2, 4, 8, 12, 24 and 48 h after thrombolysis. We used univariate and multivariable models to test the effect of BP at various time‐points on development of post‐thrombolytic sICH. Results: Prevalence of sICH in the cohort was 5.8% (ECASS‐II). Patients with sICH had significantly higher systolic BP at several time‐points after IVT compared with those without sICH ( P < 0.01 at 2 and 4 h; P < 0.05 at 12 and 48 h). The odds ratios for development of sICH per 10 mmHg increase in BP were 1.14 [95% confidence interval (CI), 1.03–1.25], 1.14 (95% CI, 1.03–1.25), 1.12 (95% CI, 1.01–1.23) and 1.12 (95% CI, 1.01–1.23), respectively. At 8 h, we observed a trend ( P = 0.07) for ECASS‐II and a significant effect ( P < 0.05) for National Institute of Neurological Disorders and Stroke, and Safe Implementation of Thrombolysis in Stroke criteria. Thus, the only time‐point with no difference observed was 24 h. Conclusions: Patients with post‐thrombolytic sICH have significantly higher systolic BP at several time‐points compared with patients without sICH.